Religious Moderation in War Phenomena Takjil Ramadan 2024 in Social Media Tiktok - Ayuk Yulia Saprianti; Ita Rodiah (Journal of Islamic Psychology and Behavioral Sciences, 2025)
The phenomenon of "war takjil" involving non-Muslim participation in the hunt for takjil (fast-breaking food) during the month of Ramadan is an interesting object of research. This reflects the social, cultural, and perhaps economic dynamics that occur in a pluralistic society. The objectives of this research can vary, depending on the perspective that is to be taken. The following is the formulation of the research objectives, Identifying how the Muslim community views this phenomenon, whether they see it positively, neutrally, or whether there is social tension that arises. Exploring social aspects and cultural perceptions related to this phenomenon. This perception will reflect the values of tolerance, religious exclusivity, and social dynamics in a multicultural society. Using the theory of Social Tolerance to understand how religious differences are managed in the same public space. Some research questions that can be asked include How does the Muslim community interpret the participation of non-Muslims in war takjil activities? Is this phenomenon considered a form of tolerance, just a trend, or a violation of religious values? Are there differences in perception among Muslim communities based on age, education level, or religious background that are more conservative compared to moderate?With these questions, it is hoped that this study can provide deeper insights into interfaith social interactions during the holy month of Ramadan.